The mitochondrial environment is required for activity of the cholesterol side-chain cleavage enzyme, cytochrome P450scc. - Black, S M (1994)
Steroidogenesis is initiated by the conversion of cholesterol to pregnenolone by mitochondrial cytochrome P450scc [cholesterol, reduced-adrenal-ferredoxin:oxygen oxidoreductase (side-chain-cleaving); EC 1.14.15.6]. Several subsequent steroidal conversions occur in the endoplasmic reticulum (ER), but the last step in the production of glucocorticoids and mineralocorticoids again occurs in the mitochondria. Although cellular compartmentalization of steroidogenic enzymes appears to be a feature of all steroidogenic pathways, some reports indicate that cholesterol can be converted to pregnenolone outside the mitochondria. To investigate whether P450scc can function outside the mitochondria, we constructed vectors producing P450scc and various fusion enzymes of P450scc with electron-transport proteins and directed their expression to either the ER or the mitochondria. Whether targeted to mitochondria or to the ER, plasmid vectors encoding P450scc and fusion proteins of P450scc with either mitochondrial or microsomal electron-transport proteins produced immunodetectable protein. When expressed in mitochondria, all of these constructions converted 22-hydroxycholesterol to pregnenolone, but when expressed in the ER none of them produced pregnenolone. These results show that P450scc can function only in the mitochondria. Furthermore, it appears to be the mitochondrial environment that is required, rather than the specific mitochondrial electron-transport intermediates.